The effect of growth stimulators on the quantitative characteristics of planting material of pinus sylvestris in the North-Kazakhstan region - S. A. Kabanova; M. A. Danchenko; A. N. Kabanov (Новые технологии, 2018)
The aim of the research has been to determine optimal methods of presowing treatment of seeds of Pinus sylvestris by various growth stimulators. The growth and survival rate of seedlings grown from seeds treated with growth stimulators have been observed for two years. High survival rate of two-year seedlings of Pinus sylvestris has been observed in variants with soaking and spraying seeds in extrasol (54.9 - 73.7%). Also it is possible to note variants with soaking in a humate for 18 hours with a survival rate of 59.0% and with watering soil with АridGrow activator (59.9%). Two-year seedlings have shown the longest roots and trunks when soaked in GNB stimulant (5 minutes), in humate (18 hours) and watering the soil with AridGrow (8.6 cm). The average wet weight of the stems ranged from 1.1 g when spraying seeds with a 0.05% solution of extrasol to 2.5 g when watering with АridGrow. When sprinkling seeds with extrasol in another concentration (0.1%), the weight of the trunks and roots was on the second place, 2.1 and 0.3 g respectively. From all the variants of the experiment only one variant (spraying with extrasol of 0,05%) lagged behind the control seedlings. Correlation analysis has shown that the length and weight of the trunk are closely related (correlation coefficient is 0.86), as well as the root mass and trunk weight (0.83). It’s been revealed that stimulants influence the growth and survival of seedlings in various ways. For the conditions of the Northern Kazakhstan presowing treatment of Pinus sylvestris seeds using soaking (5 minutes) and spraying with GNB stimulator is more preferable than soaking in humate (18 hours) and watering the soil with AridGrow activator.